2004
DOI: 10.1002/uog.984
|View full text |Cite
|
Sign up to set email alerts
|

Two‐ and three‐dimensional sonographic assessment of the fetal face. 1. A systematic analysis of the normal face

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 31 publications
5
79
0
2
Order By: Relevance
“…Surface-rendering mode in the coronal plane is useful for imaging the soft tissue surface features of the fetal face and allows rapid evaluation of the presence or absence of facial dysmorphology or clefting. 3D multiplanar imaging allows standardization of the section planes, simultaneous visualization of the three reference orthogonal planes and easy step-by-step analysis in each of the planes 3 . The introduction of 3D/four-dimensional (4D) sonography was a turning point, when surface-rendering mode began to be used to search for facial dysmorphologies and clefts.…”
Section: Letters To the Editor Facing The Next Frontier Of Fetal Magnmentioning
confidence: 99%
“…Surface-rendering mode in the coronal plane is useful for imaging the soft tissue surface features of the fetal face and allows rapid evaluation of the presence or absence of facial dysmorphology or clefting. 3D multiplanar imaging allows standardization of the section planes, simultaneous visualization of the three reference orthogonal planes and easy step-by-step analysis in each of the planes 3 . The introduction of 3D/four-dimensional (4D) sonography was a turning point, when surface-rendering mode began to be used to search for facial dysmorphologies and clefts.…”
Section: Letters To the Editor Facing The Next Frontier Of Fetal Magnmentioning
confidence: 99%
“…Some researchers 33 suggest that 3D/4D ultrasound of the fetal face does not aid diagnosis; however, others 18,34 have concluded that during routine screening when using 2D imaging techniques, the exa miner needs to image several planes and hence making the examination longer than with 3D/4D scan ning. Specifically, if using 2D imaging techniques to establish the presence of facial abnormalities of lip and nose morphology (facial dysmorphology) both the midsagittal plane and the anterior 'nose-mouth' coronal plane need to be visualized.…”
Section: Use Of Ultrasound Images Can We Use Fetal Facial Movements Fmentioning
confidence: 99%
“…CL, "both unilateral and bilateral, includes clefts involving the alveolus and hard palate anterior to the incisive foramen, namely the embryological primary palate" (Demircioglu et al, 2008). The tested rates of antenatal detection of CL range 21-30% (Rotten and Levaillant, 2004).…”
Section: Introductionmentioning
confidence: 99%